The complete book of 1950s Broadway musicals - Dietz, Dan, 1945- (Rowman and Littlefield, 2014)
This book examines in specific detail every Broadway musical which opened during the 1950s, perhaps the greatest decade for musicals-including South Pacific, The King and I, My Fair Lady, Pajama Game, Damn Yankees, and The Sound of Music. Besides te.